The German spa and health resort industry in the light of health care system reforms - Pforr, Christof; Locher, Cornelia (The Haworth Press, 2012)
The German health care system has been under increasing pressure over the past decades due to escalating health care costs. A number of reforms have been introduced to ensure a fair and sustainable financing of the health care system. These reforms also have had a significant impact on the health and wellness tourism market and pose great challenges and also new opportunities for the industry. Special reference is made to the important senior market for which health and wellness have become key aspects influencing travel behavior. This can be seen as a positive trend, particularly for the traditional spas and health resorts in Germany. However, the situation is far more complex as outlined with the case example of Bad Wörishofen.